Evaluation of Import Substitution Potential of Products from Secondary Raw Materials of Animal Husbandry - DENISSOVA, Oxana; KONURBAYEVA, Zhadyra; ZAKIMOVA, Alfiya; RAKHIMBERDINOVA, Madina (Journal of Environmental Management and Tourism, 2021)
Animal husbandry is one of the main sectors of the country's economy, which can demonstrate significant results of import substitution shortly. In article dynamics of such relative indicators characterizing scales of industrial activity in the sphere of animal industries, as a share of the branch in the Kazakhstan economy and volumes of production of animal industries per capita of Kazakhstan is considered. For example, the average annual growth rate of this indicator is compared with countries with a high level of development of this industry. It was found out that the use of secondary raw materials of animal husbandry will promote the development of new industries and import substitution of both raw materials and finished products, which will attract innovative technologies in the agro-industrial complex. The article presents a step-by-step algorithm of research of the import-substituting potential of the industry, as well as its practical testing (by the example of the Republic of Kazakhstan). Volumes of production on branch "animal industries" are defined, connections of import dependence and the agrarian production made abroad are established.